Mapping in 3D with MapIt: an added value for a professionalization path from the student perspective (Canadian Medical Education Journal, 2022)
Implication StatementDuring the pandemic, the MapIt app was integrated into an occupational therapy program to support remote learning of built environment adaptation. MapIt maps rooms in a home, then generates a 3D model for viewing and taking virtual measurements. The students express that the use of MapIt during their training leads to embodying the roles expected of an occupational therapist. To inspire other good pedagogical ideas, this article presents how MapIt can support learning in authentic situations, a key element of a professionalization path, approaching the realities experienced by patients, clients, or caregivers.